Is Alzheimer's disease genetically transmissable? New insights to the biogenesis of the disease - (:unkn) unknown (My University, 1998)
Alzheimer's disease (AD) is the most common cause of dementia in the elderly. The disease affects 1% to 6% of people over 65 years of age and 10% to 20% of those over the age of 80. AD is a slowly progressive dementia, in which memory failure, in the presence of normal alertness is the first and most notable complaint. As the disease advances, problems with language, calculation, visuospatial functions and praxis become apparent. Behavioural alterations such as depression, agitation, delusions and hallucinations become evident at any time during the course of the illness. The frequency of seizures, usually of generalised onset is about 10% and very rarely seizures may be an initial feature. The neurologic examination in AD is usually normal. Common findings are primitive reflexes and impaired graphestesia. Less common features include, extrapyramidal signs, gait disturbances and myoclonus. A definite diagnosis of AD requires pathologic confirmation on autopsy, but with suitable laboratory and diagnostic studies, 80-90% accuracy of clinical diagnosis can be achieved.
Keywords: Alzheimer's disease; Neuropathology